Patrimônio histórico e cultural ítalo-brasileiro na colônia Erechim - RS - Donin, Graziela Vitória (2019)
This research discusses the Historical and Cultural Heritage linked to the ItaloBrazilian ethnicity in the region corresponding to Colônia Erechim, located to the north of the state of Rio Grande do Sul, as well as the discussion regarding the imagetic construction of this ethnicity. brought here the Venetian universe of the great migration Veneto. The time frame refers to the twentieth century to the present day, ie, foundation and beginning of the colonization process of the Erechim Colony. This was created with the purpose of undertaking the colonization and utis possidetis of this region located in international border area, in order to obtain a human barrier against possible external invasions. Still, its integration with the capitalist system of production, to produce surpluses and basic necessities and supply the internal market. And finally, according to the positivist values of the time, the European was seen as the bearer of more advanced techniques for economic and social development, ie, superior to the caboclo and the indigenous, was the ideal type of settler. Immigration of dispossessed Italian peasants was numerically higher than the other ethnic groups, those who came here, mostly as a result of the internal migration of the Old Colonies located in the highlands. For the development of this research was made a survey of the elements that are representative of this ethnicity, such as places of memory, some linked to work ethos such as canteens, language and Gemellaggios. For the problematization of these we used documentation from the historical archives and the public authorities of the municipalities involved, such as laws, minutes and written books related to the elements. Among the main authors that support the analysis of the Italian-Brazilian peasant universe and used in this research are Tedesco (1999, 2001), Zanini (2006) and Beneduzi (2011).There was a maintenance, reproduction and reinvention of values linked to the contiguous universe of the ottocento Veneto. There is a school for the children of Italians, where classes were taught in the Talian dialect, a mutually supportive association, later converted into a sports and recreational association, but which started with an ethnic background, among other places that are configured. as places of memory and is linked to the perpetuation of the cultural signs of this ethnicity. The set of historical and cultural heritage of the Italo-Brazilian ethnicity in this colony is the object of study of this research, because it is linked to an identity invented as a strategy of social cohesion and differentiation and a feeling of nostalgia linked to the trajectory of ancestors in America.